Port Decision Maker Perceptions on the Effectiveness of Climate Adaptation Actions. Issue 3 (4th May 2018) - Ng, Adolf K.Y.; Zhang, Huiying; Afenyo, Mawuli; Becker, Austin; Cahoon, Stephen; Chen, Shu-ling; Esteban, Miguel; Ferrari, Claudio; Lau, Yui-yip; Lee, Paul Tae-Woo; Monios, Jason; Tei, Alessio; et al.
ABSTRACT: Effective adaptation to climate change impacts is rapidly becoming an important research topic. Hitherto, the perceptions and attitudes of stakeholders on climate adaptation actions are under researched, partly due to the emphasis on physical and engineering aspects during the adaptation planning process. Building on such considerations, the paper explores the perceptions of port decision makers on the effectiveness of climate adaptation actions. The findings suggest that while port decision makers are aware of potential climate change impacts and feel that more adaptation actions should be undertaken, they are skeptical about their effectiveness and value. This is complemented by a regional analysis on the results, suggesting that more tailor-made adaptation measures suited to local circumstances should be developed. The study illustrates the complexity of climate adaptation planning and of involving port decision makers under the current planning paradigm.